Answer:
a =
- b
Step-by-step explanation:
Given
c(a + b) - d = f ( add d to both sides )
c(a + b) = f + d ( divide both sides by the multiplier c )
a + b =
( subtract b from both sides )
a =
- b
Answer:
G'(1, 3)
Step-by-step explanation:
Counterclockwise rotation 90°: (x, y) ⇒ (-y, x)
So the point G is transformed to ...
... G(3, -1) ⇒ G'(1, 3)
Answer:
15
Step-by-step explanation:
Answer:
<h2>The slope is 2</h2>
Step-by-step explanation:
Step one:
we are required to find the slope of the given data points
A(4,6) B(5,8)
hence the x and y values correspond to
x1=4
y1=6
x2=5
y2=8
Step two:
Required is the slope which is
slope= y2-y1/x2-x1
Slope=8-6/5-4
Slope= 2/1
<em><u>Hence the slope of the ordered pair is 2</u></em>
ANSWER
![y = \frac{1}{3} \cos(x) - 2](https://tex.z-dn.net/?f=y%20%3D%20%20%5Cfrac%7B1%7D%7B3%7D%20%20%5Ccos%28x%29%20%20-%202)
EXPLANATION
If the graph of y=cosx is transformed to y=a cos (x−c)+d by a vertical compression by a factor of 1/3 and a translation 2 units down,
then
a=1/3
and d=-2.
The 'c' is a phase shift since it is not given, it means it is zero.
Therefore the new equation is:
y=1/3cos(x-0)−2
This simplifies to:
y=1/3cosx−2
The correct option is C.